PELATIHAN PENGGUNAAN WEBSITE WORDWALL DALAM MENDESAIN MEDIA PEMBELAJARAN - Fathor Rohman; Akmal Rizki Gunawan Hasibuan; Abdul Ghofur (Al-Ihsan: Journal of Community Development in Islamic Studies, 2023)
Sindangsari village, Cabang Bungin is one of the areas in Bekasi district where this village is still thick with a rural feel, but as technology develops in the current industrial revolution 4.0 we also pay attention to digital literacy that must be implemented so that village communities are able to follow and adapt to technological sophistication. In the world of education that must be developed through digital utilization, therefore the researchers here refer to the training method. Training on using the wordwall website in designing learning media. This training is expected to be able to provide new innovations for elementary school educators in sindangsari village so that the wordwall website here can be applied during the teaching and learning takes place because of the advantages of this wordwall website, namely providing interesting features that can support teaching and learning process activities. Interesting features are also considered practical in its manufacture, therefore the wordwall website is very suitable as a learning medium in the current industrial revolution 4.0 era. The wordwall website also received a positive response from elementary school educators in sindangsari village because the wordwall website is considered to provide a new color in the world education so that the application of learning in the classroom does not seem monotonous